Complacency is really dangerous: Three great economic crises - Frank Milne (Queen's University, Department of Economics, 2016)
The conventional discussion of the international financial crisis that erupted in the summer of 2007 is that few professional economists saw it coming, nor anticipated its ferocity in devastating the US and European economies and financial systems, leading to civil unrest and fears of greater violence in the EU. Why weren't the authorities and public warned before mid-2007? At the time, a tiny number of vocal Cassandras who delivered warnings in the media were roundly ridiculed. Now these prophets are lauded in the media. What is not widely appreciated is that there were far more professionals who gave private warnings to the large financial institutions, government regulators and central banks. These people tender their analysis in private because professional analyses of dangerous economic risks are subtle, and potentially incendiary in the hands of political populists, irresponsible media pundits and corrupt vested interests. The last thing any prudent professional would wish is to precipitate a panic. It is a tragedy that many of those who gave private warnings, were ignored, ridiculed, or in some cases, lost their jobs for challenging the financial and economic conventional wisdom. It may have been conventional, but it was far from wisdom. Because the economic crisis is continuing and imposing large costs on Western societies, it is crucial to listen again to the Cassandras. More importantly, there is not one, but three separate crises - International Private Debt, International Productivity and Income Distribution, and Western Fiscal Policy. These three crises appear to be quite separate in origin and have been brewing for decades, but the economic stresses they impose have interacted, greatly increasing their impact. The consequences of these crises for the Australian economy could be severe. Although many in the Australian establishment have boasted that Australia is relatively immune: it is a "Lucky Country", and has avoided the crises through wise policy, this is at best a partial truth. Professionals within and outside Australia have been warning for years that the country is not immune: downside risks have been increasing. Complacency is really dangerous.
Keywords: E66; G18; G28; 330; Australia; Financial Crisis; Productivity; Fiscal Policy